1998
DOI: 10.5144/0256-4947.1998.531
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Breast Cancer in Saudi Arabia: A Call For Improvement

Abstract: In carefully studied populations of the world, the incidence of breast cancer among women has shown an increase of 50% from 1960 to 1995. However, through screening programs and highly specialized, experienced multi-disciplinary teams using all modern diagnostic and therapeutic modalities available, the mortality has decreased and the relative survival (at 2, 5 and 10 years) has increased in this period.If age-specific incidence rates for Japan and USA were applied to the estimated female Saudi population in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…At King Faisal Specialist Hospital & Research Center (KFSH&RC), eight to ten newly diagnosed breast cancer patients are seen weekly in the combined breast clinic, most of them referred from other hospitals after initial management. In 1998 Jiffry et al [5] demonstrated that the majority of the referred patients had had management that is suboptimal by internationally accepted standards. Since then, we have intensified our personnel contacts with the referring surgeons, and we have performed a number of outreach visits to several areas around the country with lectures about the baseline management of breast cancer.…”
mentioning
confidence: 99%
“…At King Faisal Specialist Hospital & Research Center (KFSH&RC), eight to ten newly diagnosed breast cancer patients are seen weekly in the combined breast clinic, most of them referred from other hospitals after initial management. In 1998 Jiffry et al [5] demonstrated that the majority of the referred patients had had management that is suboptimal by internationally accepted standards. Since then, we have intensified our personnel contacts with the referring surgeons, and we have performed a number of outreach visits to several areas around the country with lectures about the baseline management of breast cancer.…”
mentioning
confidence: 99%
“…In a developing country like SA a proportion of breast surgeries are performed at low‐volume community hospitals with a less than optimal axillary lymph node retrieval 20 . In our series, where some patients are operated prior to referral to our center, 18% had inadequate axillary dissection, that is <10 lymph nodes.…”
Section: Discussionmentioning
confidence: 71%